2018
DOI: 10.1080/10428194.2018.1508672
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance rituximab in newly diagnosed mantle cell lymphoma patients: a real world analysis from the Czech lymphoma study group registry

Abstract: We analyzed 495 MCL patients from the Czech Lymphoma Study Group data registry. With the median follow-up of 4.4 years, 51.7% patients progressed or relapsed and 34.1% died. Five-year overall survival reached 65.3% and five-year progression free survival 44.1% of the patients. Maintenance rituximab (MR) after first line therapy improved overall and progression free survival compared to the patients under observation only (both p < .001). Elevated beta-2-microglobulin (p = .003), presence of systemic symptoms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Blastoid morphology and high MIPI remain important negative prognostic factors irrespective of the front-line therapy. This is equivalent to the results of other population-based studies analyzing biologic prognostic factors ( 7 , 8 , 11 ). The lack of difference in outcomes between patients with low and intermediate MIPI might be a consequence of the low number of treated patients with very favorable disease characteristics in our study, but although not always stated explicitly, seems also to have been noted in other real-life studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Blastoid morphology and high MIPI remain important negative prognostic factors irrespective of the front-line therapy. This is equivalent to the results of other population-based studies analyzing biologic prognostic factors ( 7 , 8 , 11 ). The lack of difference in outcomes between patients with low and intermediate MIPI might be a consequence of the low number of treated patients with very favorable disease characteristics in our study, but although not always stated explicitly, seems also to have been noted in other real-life studies.…”
Section: Discussionsupporting
confidence: 75%
“…With rituximab maintenance, we observed improved EFS, but not OS. Other real-life studies found improvement in both EFS and OS ( 7 , 10 , 11 ). The lack of effect on OS in our study might be due to short follow-up, but in at least one real-life study maintenance influenced neither OS nor EFS ( 8 ).…”
Section: Discussionmentioning
confidence: 81%
“…Bortezomib, in combination with cyclophosphamide, doxorubicin, and prednisone (so-called VR-CAP), was the only immunochemotherapy regimen that was associated with prolonged overall survival (OS) compared to R-CHOP in a phase III randomized trial [95]. Elderly patients treated with an R-CHOP-like regimen benefit from RM [5,96,97,98]. Maintenance therapies other than rituximab are currently tested in diverse clinical trials including lenalidomide or bortezomib [99,100].…”
Section: Current Treatment Approaches and Outcomes Of Patients Aftmentioning
confidence: 99%
“…Details about the development and operation of the CLSG lymphoma registry have been published elsewhere [ 2 , 17 , 18 ]. Briefly, the CLSG database is a nation‐wide prospectively operated registry collecting data since 1999.…”
Section: Methodsmentioning
confidence: 99%